Rancang Bangun Website Dinas Kehutanan Dan Perkebunan Kota Pagar Alam Menggunakan PHP Dan MySQL - Desi Puspita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2016)
Forestry and Estate Crops Office of Pagar Alam City is a government institution that carries out the authority of regional autonomy and helps the city government of Pagar Alam in the field of forestry and plantation. With the development of technological progress, Forestry and Estate Crops Office of Pagar Alam need to promote itself through an online website on the Internet. With an online website on the internet, people can easily access and know everything about Forestry and Estate Crops Office of Pagar Alam City quickly without requiring much time